2014
DOI: 10.1016/j.cub.2014.05.069
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Control of Cortical Actin Nucleation

Abstract: SummaryThe contractile actin cortex is a thin layer of actin, myosin, and actin-binding proteins that subtends the membrane of animal cells. The cortex is the main determinant of cell shape and plays a fundamental role in cell division [1–3], migration [4], and tissue morphogenesis [5]. For example, cortex contractility plays a crucial role in amoeboid migration of metastatic cells [6] and during division, where its misregulation can lead to aneuploidy [7]. Despite its importance, our knowledge of the cortex i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
274
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(292 citation statements)
references
References 37 publications
15
274
3
Order By: Relevance
“…In addition to the activation of ezrin, active RhoA also activates another RhoA effector protein, formins, which are essential for the regrowth of actin filaments at the retracting membrane. 18,19 In the expanding phase of membrane blebs, we found that Rnd3 is recruited to the expanding plasma membrane. The membrane localization of Rnd3 was gradually lost when reassembly of actin filaments started (Fig.…”
Section: Rhoa-rock-rnd3 Feedback Loop Regulates the Expansion And Retmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition to the activation of ezrin, active RhoA also activates another RhoA effector protein, formins, which are essential for the regrowth of actin filaments at the retracting membrane. 18,19 In the expanding phase of membrane blebs, we found that Rnd3 is recruited to the expanding plasma membrane. The membrane localization of Rnd3 was gradually lost when reassembly of actin filaments started (Fig.…”
Section: Rhoa-rock-rnd3 Feedback Loop Regulates the Expansion And Retmentioning
confidence: 84%
“…Subsequently, Stastna et al and Bovellan et al demonstrated that formin family proteins, key regulators of actin nucleation, are recruited to the membrane blebs and essential for the reassembly of actin filaments. 18,19 In addition, Logue et al showed that Eps8, a plus end capping protein, is recruited to the plasma membrane on a similar timescale as ezrin and essential for the formation of membrane blebs. 20 Thus, important regulators of actin cortex during membrane blebs were identified; however how these proteins are coordinated during reassembly of actin filaments in membrane blebs has remained unclear.…”
Section: The Regulation Of Actin Cytoskeleton During Membrane Blebbingmentioning
confidence: 99%
“…The cortical cytoskeleton is generated by both ARP2/3 and formin activity at the plasma membrane, creating meshwork of short filaments [12][13][14] . The meshwork is approximately 100 nm thick, has a pore size of about 50 nm and attaches to the plasma membrane via ezrin, moesin and class I myosins [15][16][17] .…”
Section: [H1] Structure Of the Cortical Cytoskeletonmentioning
confidence: 99%
“…The membrane models mentioned above have by-and-large neglected this active nature of the actin cortex where actin filaments are being continuously polymerized and depolymerized (18-21), in addition to being persistently acted upon by a variety of myosin motors (22-24) that consume ATP and exert contractile stresses on cortical actin filaments, continually remodeling the architecture of the cortex (4, 21, 25). These active processes in turn can generate tangential stresses and currents on the cell surface, which could drive the dynamics and local composition of membrane components at different scales (22,(26)(27)(28)(29).Actin polymerization is proposed to be driven at the membrane by two nucleators, the Arp2/3 complex, which creates a densely branched network, as well as formins that nucleate filaments (18,21,30). A number of myosin motors are also associated with the juxtamembranous actin cortex, of which nonmuscle myosin II is the major component in remodeling the cortex and creating actin flows (4,23,25,26,31,32).…”
mentioning
confidence: 99%
“…The membrane models mentioned above have by-and-large neglected this active nature of the actin cortex where actin filaments are being continuously polymerized and depolymerized (18)(19)(20)(21), in addition to being persistently acted upon by a variety of myosin motors (22)(23)(24) that consume ATP and exert contractile stresses on cortical actin filaments, continually remodeling the architecture of the cortex (4,21,25). These active processes in turn can generate tangential stresses and currents on the cell surface, which could drive the dynamics and local composition of membrane components at different scales (22,(26)(27)(28)(29).…”
mentioning
confidence: 99%